Modelling feed resources budgets in the moist savannahs of West Africa - Naazie, A.; Smith, Jimmy W. (International Grassland Society, 1997)
A deterministic model was developed to evaluate the adequacy and utilization of ruminant livestock feed resources in the moist savannahs of W. Africa. Changes in land cropped and available as range, were used to project changes in feed resources over time and to evalaute whether these feed resources were adequate for the expected numbers of livestock in the region. Ignoring crop residues as feed resources would result in feed shortages especially in the drier northern parts of the moist savannahs. If 50 percent of the residues could be used as feed, feed shortage would be unlikely irrespective of area cropped. In that case range resources lost through expansion of cropped area are effectively substituted for by the resulting crop residues. Research on how much residues can be used as livestock feed without affecting land productivity is warranted.